Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 1 - Test: 26

Answer

-1

Work Step by Step

Substitute x = 6, y = -2, and z = -3. $\frac{y + z - 1}{x} = \frac{-2 + (-3) - 1}{6} = \frac{-5 - 1}{6} = \frac{-6}{6}$ = -1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.